Research Outlines of the Sustainable Profile of Believers in Croatia - Brstilo Lovrić, Ivana; Brgles, Miriam Mary; Mravunac, Damir (Studia Ecologiae et Bioethicae, 2024)
The topic of this paper are sustainable habits and attitudes of the religious population in Croatia regarding the Encyclical Letter Laudato Si’. Empirical work is based on CRO Laudato Si' project using survey method on a non-probabilistic sample of the religious population in Croatia, which in this paper are operationalized as active and occasional believers according to their regularity of attending religious ceremonies (N=1305). The analysis showed that active believers have a more pronounced sustainable profile (as they throw away less food, separate waste more, show greater readiness for saving water, electrical energy and have a more pronounced critical attitude about the need for greater application of the Laudato Si' within the Church and society) than the occasional believers. Given the nonrepresentative sample, the presented data cannot be generalized to the religious population in Croatia, shaping its fundamental contribution in stimulating future scientific analyses and reflections on the Church's relationship with religious practices, and emphasizing active believers as potential social leaders of sustainable lifestyles. Therefore, the sustainable habits of the surveyed believers represent a relational good and serve as the basis for building a culture of moderation that respects key principles of Catholic Social Teaching. In that perspective, we conclude that it is important for the Church to speak more often about the socio-environmental crisis and encourage strong responses to the crisis at all social levels, from households and families to the macro level.